Incidence des caractéristiques structurales du sous-sol sur l'entrée en production de Tuber melanosporum et d'autres champignons mycorhiziens - Callot, G.; Jaillard, B.; Braye, J. P.; Jalade, M. (Agronomie, 1996)
Effect of structural characteristics of subsoil on the fruiting of Tuber melanosporum and other mycorrhizal fungi. The collection sites for ascocarps of Tuber melanosporum Vitt were noted over four consecutive years in a truffle bed of live oaks (Quercus ilex) mycorrhized by T melanosporum. The mycorrhizas of Tuber and other fungi were checked 11 years after planting. At the same time, a detailed soil survey made it possible to distinguish different soil units within the truffle bed. Cartographic analysis of the data set showed that the mycorrhizal status and the location of the fungus collection sites were related to the structural characteristics of the subsoil. The presence of a slightly permeable clay subsoil discourages fruiting in both epigeal and hypogeal fungi. Soils presenting a shallow calcareous crust discourage the growth of hypogeal Tuber-type fungi, but encourage that of epigeal fungi. T melanosporum grows best in soils with a very porous horizon developed in contact with the calcareous bedrock. This horizon (termed Bbio by the authors) is characterized by an intensive biological activity.
Keywords: autoecology; fungi; limestone; Mycorrhizas; subsoil; Tuber